Children’s anxiety and factors related to the covid-19 pandemic: An exploratory study using the children’s anxiety questionnaire and the numerical rating scale - de Avila, Marla Andréia Garcia [UNESP]; Filho, Pedro Tadao Hamamoto [UNESP]; da Silva Jacob, Francine Letícia [UNESP]; Alcantara, Léia Regina Souza [UNESP]; Berghammer, Malin; Nolbris, Margaretha Jenholt; Olaya-Contreras, Patricia; Nilsson, Stefan (MDPI, 2020)
The repercussions of the COVID-19 pandemic on children’s lives deserve attention. This study aimed to assess the prevalence of anxiety among Brazilian children and its associated factors during social distancing during COVID-19. We used a cross-sectional design with an online survey from April to May 2020 in Brazil. We included children aged 6–12 years and their guardians. The Children’s Anxiety Questionnaire (CAQ; scores 4–12) and the Numerical Rating Scale (NRS; scores 0–10) were used to measure anxiety. We enrolled 157 girls and 132 boys, with a mean age of 8.84 (±2.05) years; 88.9% of respondents were mothers. Based on CAQ ≥ 9, the prevalence of anxiety was 19.4% (n = 56), and higher among children with parents with essential jobs and those who were social distancing without parents. In logistic regression, the following variables were associated with higher CAQ scores: social distancing without parents; more persons living together in home; and education level of guardians. Based on NRS > 7, the prevalence of anxiety was 21.8% (n = 63); however, no associations with NRS scores were found with the investigated variables. These findings suggest the necessity of implementing public health actions targeting these parents and their children at the population level.
Keywords: Anxiety; Children; Covid-19; Pandemic; Social isolation